Prolonged drought and recovery responses of Kentucky bluegrass and ornamental groundcovers - Domenghini, Jacob C.; Bremer, Dale J.; Fry, Jack D.; Davis, Gregory L. (My University, 2014)
Municipalities often restrict irrigation of urban landscapes, causing plants to experience drought stress. Few data are available regarding drought resistance of non-turfgrass landscape species. This study evaluated the performance of one turfgrass (Poa pratensis L. ‘Apollo’) and eight herbaceous landscape species (Achillea millifolium L., Ajuga reptans L. ‘Bronze Beauty’, Liriope muscari Decne., Pachysandra terminalis Siebold and Zucc., Sedum album L., Thymus serpyllum L., Vinca major L., and Vinca minor L.) during a severe drydown and subsequent recovery. This greenhouse study was conducted in the spring/summer and again in the fall of 2010. S. album performed the best, averaging 254 days to decline to a drought rating of 1 (1 to 9 scale, 1 = dead/dormant and 9 = best quality). L. muscari and P. terminalis also performed well, averaging 86 days to a drought rating of 1. V.minor and V.major declined faster than the previous species, averaging 63 days. A. millifolium, A. reptans, P. pratensis, andT. serpyllum declined the fastest to a drought rating of 1 (mean 52 days). Thereafter, the only species to recover after 60 days of resuming irrigation were P. pratensis [46% pot cover (PC)], S. album (38% PC), and V.major (35% PC) in the spring/summer study; no species recovered during the fall study. Results indicate S. album, L. muscari, and P. terminalis are the most drought-resistant among the species evaluated in landscapes where severe drought may occur. V. minor and V. major are good selections in less severe droughts as is P. pratensis if periods of dormancy are acceptable.
Keywords: Drought resistance; Drought resistant; Nursery and landscape plants; Severe drought; Water restrictions; Kentucky bluegrass